Genome-sequence, annotation and phylogenetic insights of the lactic acid bacterium Limosilactobacillus fermentum strain LAB1 obtained from the dairy beverage borhani - Tanim Jabid Hossain (Acta Scientiarum. Biological Sciences, 2023)
Limosilactobacillus fermentum is a promising probiotic with several documented health benefits. LAB1 is an antagonistic L. fermentum strain isolated from borhani, a traditional South Asian beverage prepared from dairy and plant ingredients. Here, I present the genome sequence of the L. fermentum LAB1 strain, its annotation, and phylogenetic features. The 2.01 Mb genome with a G+C content of 51.9% was assembled into 221 contigs and predicted to have 1,913 protein-coding genes, 98 pseudo genes, 7 rRNAs, 60 tRNAs, and 1 CRISPR array. As much as 91.1% of the coding sequences could be assigned to known functional genes. Determination of average nucleotide identity (ANI) of the genome sequence revealed 99.37% identity to that of the type strain ATCC 14931. Its 16S rRNA gene sequence extracted from the genome sequence showed close phylogenetic association with several L. fermentum strains. The genome sequence is expected to provide useful insights with regard to the phenotypic, metabolic and beneficial aspects of this lactic acid bacterium.